2015
DOI: 10.1021/acs.joc.5b00140
|View full text |Cite
|
Sign up to set email alerts
|

Construction of β-Mannosidic Bonds via Gold(I)-Catalyzed Glycosylations with Mannopyranosyl ortho-Hexynylbenzoates and Its Application in Synthesis of Acremomannolipin A

Abstract: A mild and convenient protocol for direct synthesis of β-mannosides has been developed. Glycosylation of 4,6-O-benzylidene-protected mannosyl ortho-hexynylbenzoates with various alcohol acceptors catalyzed by gold(I) complex proceeded smoothly at 0 °C to room temperature and afforded the corresponding β-mannoside in high yield and satisfactory stereoselectivity. This reaction was applied to the total synthesis of acremomannolipin A and its analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Extensive mechanistic studies have been performed on the reaction, which supports a mechanism shown in Scheme . The utility of this protocol has been demonstrated by its applications in the total syntheses of natural products including periploside A, acremomannolipin A, and trioxacarcins …”
Section: Transition Metal Catalysismentioning
confidence: 62%
“…Extensive mechanistic studies have been performed on the reaction, which supports a mechanism shown in Scheme . The utility of this protocol has been demonstrated by its applications in the total syntheses of natural products including periploside A, acremomannolipin A, and trioxacarcins …”
Section: Transition Metal Catalysismentioning
confidence: 62%
“…Recent work with gold-catalyzed glycosylations also indicate that the role of triflate in these reactions is non-trivial 20,21. Perhaps the explanation for the -selectivity is the intermediacy of an oxocarbenium ion ionpair in B 2,5 conformation 22 either solvent separated as we proposed for the 4,6-silylene donor,10 or as a contact ion pair with triflate in the a-position as recent calculations support.…”
mentioning
confidence: 64%
“…The efficacy of this glycosylation reaction was demonstrated by the efficient synthesis of ac yclic triterpene tetrasaccharide, [24] ginsenoside and chikusetsusaponin-LT8, [25] and acremomannolipin A. [26] Recently,H otha and co-workers showed that alkynyl glycosyl carbonates 7 were also stable glycosyl donors that could be activated by gold and silver salts in the presence of nucleosides, amino acids, phenols, and azides to produce the correspondingg lycoconjugates (10)i ne xcellent yields (Scheme 3). [27] The efficiency of this methodw as highlighted by the synthesis of at ridecasaccharide segmentt hat was reminiscentoft he cell surface of mycobacteria.…”
Section: O-glycosidesmentioning
confidence: 99%